Analysis of landcover changes and carrying capacity of coastal cities North Java of Central Java Province, Indonesia - Krisnanta, Anjar; Hasibuan, Hayati Sari; Tambunan, Rudi Parluhutan (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
North Coastal Central Java has been a strategic zone from the colonial era to the present because it supports the national socio-economic sector. Urbanization has threatened the development of districts/cities on the northern coast of Central Java. The physiographical conditions of coastal districts/cities along Pantura are formed from alluvial plains, making the environment's carrying capacity more vulnerable to changes in global conditions and pressures from the socio-economic activities of the population. This study aims to identify changes in land cover, its relationship to road infrastructure development, and its implications for environmental carrying capacity. The method used in this study uses GIS to determine changes in land cover and settlement growth patterns and calculates biocapacity and ecological footprint to obtain environmental carrying capacity conditions. The results show that land cover changes mainly occur in agricultural land, plantations, and settlements. In addition, the environment's carrying capacity experienced a deficit/overshoot in 2010, which continued until 2020. The result indicates the problem in the environmental dimension of sustainable development of coastal cities and requires serious intervention to increase environmental quality.